QARAQALPAQ XALÍQ PEDAGOGIKASÍNÍŃ QÁLIPLESIW TARIYXÍ HÁM OQÍWShÍ JASLARDÍ ÁDEP-IKRAMLÍQ RUWXÍNDA TÁRBIYALAWDÍŃ PEDAGOGIKALÍQ TIYKARLARÍ - Esemuratova, Turganbike Aytmuratovna (ILIM hám JÁMIYET, 2026)
This article examines the formation of Karakalpak folk pedagogy, its historical foundations, its role within the system of national values, and its significance in the moral education of students. It also analyzes the pedagogical potential of folklore, customs, traditions, and national values in fostering morality, diligence, patriotism, humanism, and the spiritual development of the younger generation.